Papillary Tumor of the Pineal Region: A Case with Unique Immunohistochemical Keratin Expression Pattern - Gupta, Rakesh Kumar; Batra, Vineeta Vijay; Srivastava, Arvind Kumar; Sharma, Mehar Chand (Indian Journal of Medical and Paediatric Oncology, 2020)
Papillary tumor of the pineal region (PTPR) is a rare neuroepithelial tumor first described in 2003. It is a newly recognized entity and introduced in the WHO classification of central nervous system tumors in 2007. Till date, about 70 cases have been described in literature. Herein, we report an additional case of PTPR in a 25-year-old male with emphasis on immunohistochemistry and ultrastructural features. Interestingly, this case showed a unique membranous as well as dot-like Golgi zone keratin (AE1/AE3 and CK18) expression pattern.
Keywords: Immunohistochemistry; keratin; papillary tumor; pineal; ultrastructure